GEOMETRI PERLAPISAN BATUPASIR KONGLOMERATAN SEBAGAI SISIPAN PADA FORMASI NANGGULAN DI KALI WATUPURU DAN KALI SONGGO, PEGUNUNGAN KULON PROGO, YOGYAKARTA - siti nuraini (KURVATEK, 2017)
Nanggulan  Conglomeratic  Sandstone  is  one  of  important  part  of     Nanggulan  Formation  which  is deposited during   Middle Eocene to early Late Eocene (Saputra & Akmaluddin, 2015) or Late Oligocene (Rahardjo, 1995). The grain composition of Nanggulan conglomeratic sandstone  is characterized by various rock fragments (metamorphic, igneous, sedimentary rocks) which mixture up to fine to coarse sand-sized matrix. Other materials present within the Nanggulan conglomerathic sandstone are shell fragments, coal remains, siderithic concretions which is deposited within high energy condition. Geometry of conglomeratic sandstone  stratification is still being  a question  among the researchers  due to discontinuous  sand body character.   To study external form of sandstone body needs to combine with internal characters such are grain texture, grain or fragment composition, sedimentary structures to predict a depositional facies. This research is dedicated to study the character of the Nanggulan conglomeratic sand body. Field geological observation was conduct to two rivers i.e Kali Watupuru and Kali Songgo where transecting the Nanggulan beds.  The  grain  or  fragments  concentration  of  Nanggulan  conglomeratic  sandstone  displays  in  various condition for example lying above an erosional surface to the bottom position, or concentrate to the upper layer. It also appears to be engaged in coarser size matrix, or displays a dense grain composition to elsewhere. Geometry of the Nanggulan conglomeratic sandstone represents a lens geometry  which pinching-out to the edge of body.   However, to the top of lens geometry were found steep joints cross cutting the sand layers. Initial geometry of Nanggulan conglomeratic sandstone indicates a channel fill shape due to filling sediments into the erosional feature of underlying beds. When lithification and compaction process occurred along the burial and uplifting tectonic phase, a channel fill geometry becomes lens geometry. Bulging to the centre part and thinning to the edge of sandstone body, is caused by differential compaction process. Lens geometry is believed as one example of structural trap model for sandstone reservoir. The occurrences of vertical joints to the Nanggulan conglomeratic sandstone need to be considered as seal potential within clossure trap or even more causing hydrocarbon leakings.  If development of vertical joint occurs along migration process, it may be potentially leak. However, if joints already sealed parts of hydrocarbon pool may create a compartmentalization  reservoir  body.  By  doing  this  investigation  could  predict  an  advance  reservoir modelling study using outcropp analogues.   Keyword: Nanggulan conglomeratic sandstone, lens geometry, sandstone body.